Collaborative Work, through Google Drive Tool, to Develop the Writing Skill in A1 level. - León Pazmiño, Ana María; Rosero, Andrea (Kronos – The Language Teaching Journal, 2018)
This quasi-experimental research has determined the incidence of collaborative work in developing the written skill, in the students of basic levels of English at university in Ecuador, by implementing collaborative work through the Google Drive tool. This research has been carried out with two groups: the control and the experimental one; each group consisted of 30 students. Both groups were given a pre and a post-test to evaluate their written performance. A rubric was used to grade their tasks. The application of the instruments permitted the researcher to proof and accept the alternative hypothesis through posing a hypothesis test, which determined that the implementation of activities based on collaborative work, through Google Drive, had a positive impact on the students’ writing performance. This can be stated by comparing the final means from the experimental group where the grades raised from 3.46 out of 10 in the pre-test to 6.34 out of 10 in the post-test. This research has confirmed the importance of working collaboratively by using technology in the development of the English writing skill.